2022
DOI: 10.3390/nu14030512
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide Reduces Weanling Pig Diarrhea in Conjunction with Improving Intestinal Antioxidase Activity and Tight Junction Protein Expression

Abstract: This study was to illustrate the effects of fructooligosaccharide (FOS) on the antioxidant capacity, intestinal barrier function, and microbial community of weanling pigs. Results showed that FOS reduced the incidence of diarrhea (6.5 vs. 10.8%) of pigs (p < 0.05) but did not affect growth performance when compared with the control group. A diet supplemented with FOS increased ileal mRNA expression of occludin (1.7 vs. 1.0), claudin-1 (1.9 vs. 1.0), claudin-2 (1.8 vs. 1.0), and claudin-4 (1.7 vs. 1.0), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…According to several contradictory studies, Serratia is detrimental to intestinal epithelial cells and can cause diarrhea in infants. Zhang, Z. et al 43 demonstrated that fructooligosaccharides can increase the population of Megasphaera and decrease the incidence of diarrheal in piglets. Staphylococcus has a positive correlation with total oligosaccharide concentration 44 , and reducing this concentration can reduce the incidence of constipation in rodents 45 .…”
Section: Discussionmentioning
confidence: 99%
“…According to several contradictory studies, Serratia is detrimental to intestinal epithelial cells and can cause diarrhea in infants. Zhang, Z. et al 43 demonstrated that fructooligosaccharides can increase the population of Megasphaera and decrease the incidence of diarrheal in piglets. Staphylococcus has a positive correlation with total oligosaccharide concentration 44 , and reducing this concentration can reduce the incidence of constipation in rodents 45 .…”
Section: Discussionmentioning
confidence: 99%
“… Prebiotic Pig Dose Stress type Effect Reference FOS Weaned piglets 2.5 mg/kg Immune stress ↑: Bacillus , Bifidobacterium (cecum), IgA, IgM, SIgA (jejunum) ↓: IL-1β, TNF-α (plasma), E. coli (cecum), IL-6 mRNA (jejunum & ileum), IL-1β mRNA (duodenum), TNF-α mRNA (jejunum & ileum & duodenum) Liu et al. (2020) FOS Weanling piglets 1% Oxidative stress ↑: Sharpea , Megasphaera , Bacillus (ileum), Nrf2 (serum) ↓: D-lactate, TNF-α (serum) Zhang et al. (2022c) FOS Weaning piglets 5 g/kg Immune stress ↑: Average daily gain, IgG (serum) Wang et al.…”
Section: Nutritional Strategies During Stressmentioning
confidence: 99%
“…During immune stress induced by ETEC, supplementation with FOS at 2.5 mg/kg decreased interleukin-1β and TNF-α, and increased jejunal immunoglobulins ( Liu et al., 2020 ). In diarrheal weanling piglets, a diet containing 1% FOS improved expression of Nrf2 and reduced diarrhea incidence ( Zhang et al., 2022c ).…”
Section: Nutritional Strategies During Stressmentioning
confidence: 99%
“…The RNA extraction, reverse transcription and real-time PCR procedures were performed according to a previous study. 8 GAPDH was used as the reference gene. All the primers chosen to study the expression of genes related to inflammatory responses, host defense peptides, tight junction proteins and mucins, as listed in ESI Table S2, † were synthesized by Generay Company (Shanghai, China).…”
Section: Mrna Expression Of the Intestinal Barriermentioning
confidence: 99%
“…6,7 Our previous study found that adding FOS in the diet of weanling pigs improved the antioxidant capacity and reduced pig diarrhea by improving the expression of tight junction proteins and the abundance of lactic acid-producing bacteria in the intestine. 8 However, few studies have compared the mechanisms of different oligosac-charides on the performance, intestinal health and microbial community of the host. Therefore, this study was conducted to investigate the effects of xylo-oligosaccharides (XO), isomaltooligosaccharides (IM) and mannan-oligosaccharides (MO) on the growth performance, diarrhea incidence, intestinal integrity, immune function, and microbial community of weanling piglets.…”
Section: Introductionmentioning
confidence: 99%